Analysis of Minimum Service Standards on General Patients’ Revisit Intention at the Outpatient Department of RS Grandmed Lubuk Pakam in 2026. - Putri Maharani; Ramadhani Sitepu; Tati Murni Karokaro (JURNAL KESMAS DAN GIZI (JKG), 2026)
This research aimed to examine the influence of Minimum Service Standards (MSS), which include human resources, facilities and infrastructure, management and governance, and budget, on the revisit intention of general outpatients at RS Grandmed Lubuk Pakam in 2026. The study applied a quantitative method using a cross-sectional design. The population consisted of all general patients who had made repeat visits, with a sample of 95 respondents selected through purposive sampling. Data were gathered using structured questionnaires and analyzed through the Chi-square test for bivariate analysis and multiple logistic regression for multivariate analysis. The results of the univariate analysis indicated that most respondents considered human resources (75.8%), facilities and infrastructure (80.0%), management and governance (60.0%), and budget (71.6%) to be in poor condition. In addition, the majority of respondents showed a low level of revisit intention (54.7%). The bivariate analysis demonstrated significant associations between human resources (p=0.006), management and governance (p=0.017), and budget (p=0.007) with revisit intention. Meanwhile, facilities and infrastructure did not show a significant relationship with revisit intention (p=0.081). The multivariate analysis revealed that human resources had a significant impact on revisit intention (p=0.041), whereas management and governance and budget variables were not statistically significant. In summary, human resources were identified as the most influential factor affecting revisit intention among general outpatients. Therefore, efforts to improve staff competence, professionalism, and service attitudes should be prioritized in order to strengthen patient loyalty and promote repeat visits.